Transmission de la langue slovene dans la communauté slovene a Paris - Cibrić, Lea (Vestnik za tuje jezike, 2017)
The purpose of this article is to present the results of the research on the transfer of Slovene among the Slovenes in Paris. First we discuss the Slovenian immigration, then we take into account various sociolinguistic issues, and the main part of the article is devoted to the analysis of interviews. One of the effects of immigration is the lack of opportunities for the use of Slovene. French, as the language of the environment, prevails in the working environment and also helps create social ties. Family language policies of non-transmission of mother tongues may arise as a result of mixed marriages - if parents do not speak the same language, the Slovene language loses the battle with French, which becomes the language of communication. We noticed that in some cases this prevails, but the Slovenian parents in Paris are extremely persistent and, in most cases, Slovene is transferred. However, it should be acknowledged that the level is not always the highest, since the younger generations are not in regular contact with Slovenia. All in all, it is certainly encouraging to know the important role of Slovene in the Parisian community of the Slovenes and that the Slovenian culture is being transferred to next generations.
Keywords: Slovenes; Slovenci; Paris; Pariz; slovenski izseljenci; Slovene emigrants; emigration; izseljenstvo; slovenščina; Slovene; sociolinguistics; sociolingvistika